PENGARUH JENIS KELAMIN DAN KREATIVITAS TERHADAP KEMAMPUAN MENGEMUKAKAN PENDAPAT ANAK KELAS RENDAH DI SEKOLAH DASAR - , Karnadi (Pendidikan Dasar, 2009)
Abstract, The objective of this research is to find out the differences of early childhood students’ ability in expressing opinion based on the effect of sexual difference and creativity. The method used in this research is ex post facto 2 x 2 factorial design and selected randomly of 64 students from 5 equal elementary schools.The research findings are follow: (1) Male students’ ability in expressing opinion are higher than those female students; (2) Male student’s ability in expressing opinion are higher than those female students, for those who have high creativity; (3) There is no significance difference between male and female student’s ability in expressing opinion, for those who have low creativity; (4) There is no significance interaction effect between sexual different and level of students’ creativity.These findings come up with a conclusion that when a teacher want to improve students’ (early childhood students) ability in expressing opinion, especially in democratic era, level of creativity could not be taken into consideration, if student’s sexual different is compared.